Poppers, the Politics of Exemption and the Characteristics of Poppers Users in the annual English Festival Study, 2014–23 - Measham, Fiona (The British journal of criminology, 2025)
This paper explores the relationship between socio-demographic characteristics, self-reported alkyl nitrite (‘poppers’) use and sexual behaviours against a backdrop of UK policy change and ambiguity surrounding legal status. In 2024, the Advisory Council on the Misuse of Drugs recommended a unique, government-initiated, legal exemption from the Psychoactive Substances Act 2016 for poppers, because of its use by gay and bisexual men to reduce the risk of injury during anal sexual intercourse. Data from the annual convenience sample English Festival Study 2014-23 (n = 11,566) were used for Bayesian regression analyses of self-reported poppers use in three-time frames: lifetime, past year and past month use. Gay men were significantly more likely to report poppers use and particularly those reporting past-year participation in anal sex. Providing a critical analysis of recent trends in UK drug policy, the authors highlight how differential discrimination occurs within drug control where targeted exemption meets the politics of protected characteristics in UK law. This paper argues that poppers, therefore, provide a unique example in UK drug policy of how an apparent liberalization of legislative control could bolster the overarching drug prohibition regime while maintaining the appearance of rationality and fairness.